(untitled) - Nakayama, Ichiro (Tokyo, 1964)
Contents: Beginning with a discussion of the postwar rehabilitation of the Japanese economy, Nakayama continues with an examination of the traditional Japanese society and the long-term factors affecting industrial growth, and concludes with a consideration of Japan's future in industrialization of Japan's future in industrialization
Keywords: Japan,Nhật Bản; Economic conditions,Điều kiện kinh tế; 1945-1989,1945-1989